How financial liberalization impacts stock market volatility in Africa: evidence from Nigeria - Patrick Olufemi Adeyeye; Olufemi Adewale Aluko; Oladapo Fapetu; Stephen Oseko Migiro (Investment Management & Financial Innovations, 2017)
Understanding the impact of financial liberalization on stock market is important for decision making by investors. The neo-classical economists believe that financial liberalization reduces stock market volatility while the post-Keynesian economists argue that financial liberalization increases volatility of the stock market. This study investigates the effect of financial liberalization on the volatility of an emerging stock market in Africa, with particular focus on the Nigerian stock market. The estimation results reveal that financial liberalization has a significant positive impact on return volatility, thus indicating that it increases stock market volatility. Also, the study finds no evidence of asymmetry in the stock market.